A formal [3+2] cycloaddition reaction of N-methylimidazole as a masked hydrogen cyanide: access to 1, 3-disubstitued-1H-1, 2, 4-triazoles. Issue 64 (13th July 2020) - Yavari, Issa; Khaledian, Omid
Abstract : N -Methylimidazole (NMI) can act as a masked HCN in the synthesis of 1, 3-disubstitued-1 H -1, 2, 4-triazoles via a formal cycloaddition reaction of hydrazonoyl chloride with NMI. Abstract : N -Methylimidazole (NMI) can act as a masked HCN in the synthesis of 1, 3-disubstitued-1 H -1, 2, 4-triazoles via a formal cycloaddition reaction of hydrazonoyl chloride with NMI. The product was proved to be formed via an initial nucleophilic substitution of hydrazonoyl chloride with NMI following cyclization and two sequential C–N bond cleavages.